The The Role of Women in The Preservation of Dayak Desa Ikat Weaving: (Study in Tapang Sambas-Tapang Kemayau Village Sekadau District West Kalimantan) - Kwirinus, Dismas; Peri, Heribertus (Jayapangus Press, 2023)
This study aims to determine the role of Village Dayak women in preserving ikat in the village of Tapang Sambas – Tapang Kemayau, Sekadau District, West Kalimantan. This research is a qualitative research, namely a study where the data is not in the form of numbers and usually emphasizes understanding and interpreting the meaning of an interaction event of human behavior. The type of research used is the type of case study. The sampling technique is using snowball sampling. Based on the results of the research it is known that the role of women in preserving the Dayak Ikat weaving, starting from the initial process of rolling the thread until it is finished being a cloth, only women weave the cloth because in general men are not allowed to participate in weaving because there are prohibitions and restrictions that must be obeyed. We can already see the participation and involvement of weavers in efforts to preserve this Dayak woven fabric. Weaving craftsmen are active in participating in training activities, cultural performances and cultural exhibitions. The philosophical values offered in this weaving tradition can be seen in the spirit of mutual cooperation and solidarity among Dayak Desa women.